Tradition and nutrition: How Aceh’s culture shape child condition - Nouval Ramadhan; Rosaria Indah; Marisa Marisa (AcTion: Aceh Nutrition Journal, 2025)
The prevalence of stunting cases in Aceh is still very high at 29,4% (2023).  One of the social factors that influence stunting is the local culture in feeding practices. This study aimed to determine the culture that influences feeding practices among children diagnosed with stunting. Qualitative research using ethnographic tools was conducted in Kota Sigli, Aceh in 2022. Data were collected through 112 hours of observation, semi-structured interviews with eight mothers of stunted children, and informal interviews with five community leaders. The data were analyzed using NVivo, and several themes were generated. Results: Child-feeding culture in Aceh plays a role in child growth, both positively and negatively. The tradition of peucicap with dates and breast milk contributes to gut health through the production of bacteriocins that inhibit the growth of pathogenic bacteria. The 'rice and water' belief encourages breastfeeding from both breasts, increasing colostrum production. The consumption of star gooseberry leaves and banana rice mix contributes to increased weight gain in children. However, some practices, such as ie mom adék and poor hygiene habits, can have a negative impact. Meanwhile, other cultures, such as peutrôn tanôh and superstitious beliefs, tend to be neutral towards child growth. In conclusion, the local culture in Aceh influences the feeding of stunted children, with positive, negative, or neutral effects, depending on practices such as peucicap, consumption of star gooseberry leaves, or poor hygiene.